2018
DOI: 10.1016/j.ijvsm.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oviduct and follicular fluids on ram sperm capacitation and acrosome reaction in vitro

Abstract: The present study was designed to study the influence of different concentrations of oviduct fluid (OF) and follicular fluid (FF) on ram sperm capacitation and acrosome reaction in vitro. Forty semen samples were collected from three Barki rams throughout the period of study (10 weeks). Fresh semen was evaluated, layered under S-TALP (sperm Tyrode’s albumin lactate pyruvate) medium and subjected to swim up techniques. Split fractions of semen were incubated in media enriched with different levels of OF (10, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It is well established that FF enhances the ability of spermatozoa to undergo capacitation, acrosomal reaction [ 1 , 62 , 63 ] and supports sperm motility [ 64 ]. Furthermore, previous studies have demonstrated that progesterone is the main active component of FF affecting different functional properties of spermatozoa such as capacitation and acrosome reaction [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that FF enhances the ability of spermatozoa to undergo capacitation, acrosomal reaction [ 1 , 62 , 63 ] and supports sperm motility [ 64 ]. Furthermore, previous studies have demonstrated that progesterone is the main active component of FF affecting different functional properties of spermatozoa such as capacitation and acrosome reaction [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern breeding systems require, nowadays, the diffusion of superior genotypes and thus the selection of high quality gametes and embryos. In male reproduction, many factors such as routine procedures of handling and storage, might affect negatively the quality of spermatozoa, and several strategies have been designed to overcome these limitations in order to achieve high in vivo and in vitro fertility rates [21], [22]. Among others, sperm purification and sorting represent a valid tool for the selection of sub-populations of the best spermatozoa (in terms of motility and morphology) within an ejaculate and the discard of defective cells, contaminations and debris.…”
Section: Nanotechnologies For Sperm Purification and Sorting In Farm mentioning
confidence: 99%